2014
DOI: 10.3174/ajnr.a4053
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction in CT-Guided Spine Biopsies Does Not Reduce Diagnostic Yield

Abstract: BACKGROUND AND PURPOSE:CT-guided biopsy is the most commonly used method to obtain tissue for diagnosis in suspected cases of malignancy involving the spine. The purpose of this study was to demonstrate that a low-dose CT-guided spine biopsy protocol is as effective in tissue sampling as a regular-dose protocol, without adversely affecting procedural time or complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…12 In another study of two techniques of CT-guided spine biopsies by Shpilberg et al, the mean duration of the procedure was found to be 34.31 ± 12.19 minutes for the low-dose group versus 38.17 ± 8.92 minutes for the regular-dose group. 13 In our study, the mean time taken for biopsy was slightly longer than in other recent studies (44.6 minutes). This could be accounted for by various technical differences, foremost among which is that we did not use CT fluoroscopy for the biopsies.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…12 In another study of two techniques of CT-guided spine biopsies by Shpilberg et al, the mean duration of the procedure was found to be 34.31 ± 12.19 minutes for the low-dose group versus 38.17 ± 8.92 minutes for the regular-dose group. 13 In our study, the mean time taken for biopsy was slightly longer than in other recent studies (44.6 minutes). This could be accounted for by various technical differences, foremost among which is that we did not use CT fluoroscopy for the biopsies.…”
Section: Discussioncontrasting
confidence: 64%
“…In the context of vertebral biopsies, this was also studied by Shpilberg et al who found a statistically significant difference between the low-dose (80 kVp, 40-60 mAs) and regular-dose (120 kVp, mAs > 200) groups in total CTDI vol (69.47 ± 24.76 mGy for low dose vs. 285.2 + 132.6 mGy for regular dose; p < 0.0001). 13 Also, newer generations of CT scanners involve markedly lower radiation doses as compared with older devices. This was demonstrated in a study by Guberina et al, who found CTDI vol was 13.3 mGy on a 64-slice CT scanner compared with 14.4 mGy on a 4-slice CT scanner.…”
Section: Discussionmentioning
confidence: 99%
“…The use of potentially harmful ionizing radiation should also be taken into account. 8 Culture Yield of Percutaneous Image-Guided Biopsy: The Actual Numbers A crucial topic is the culture yield of the spinal or paraspinal biopsy samples that have been obtained. According to a meta-analysis that included 33 studies, image-guided biopsy has a positive culture yield of 48%.…”
Section: Arguments For Routinely Performing Percutaneous Image-guided Biopsymentioning
confidence: 99%
“…Previous work has shown the success of low-dose protocols in a variety of procedural settings, including CT-guided spine procedures [5, 6] and CT-guided lung biopsies [79]. However, the previous work with low-dose CT-guided lung biopsies was limited by small sample sizes, relatively short follow up periods to evaluate dose reductions, and limited analysis of the effect of a standardized low-dose protocol on multiple operators.…”
Section: Introductionmentioning
confidence: 99%